دور الألعاب التعليمية في تنمية الحصيلة اللغوية لأطفال أقسام التربية التحضيرية من وجهة نظر مربيات التربية التحضيرية - جديدي,عبد الغنى (University of Eloued جامعة الوادي, 2024)
تهدف الدراسة الحالية إلى معرفة دور الألعاب التعليمية في تنمية الحصيلة اللغوية لدى أطفال أقسام التربية التحضيرية من وجهة نظر مربيات التربية التحضيرية، وقد تكونت عينة الدراسة من (80) مربية بأقسام التربية التحضيرية، تم توظيف المنهج الوصفي في إجراء هذه الدراسة، كما استخدم الباحث استبيانا كأداة لجمع البيانات من إعداده، وقد توصلت نتائج الدراسة إلى أنّ تقدير المربيات كان بدرجة عالية لدور الألعاب التعليمية في تنمية الحصيلة اللغوية لدى أطفال أقسام التربية التحضيرية سواء لبعد الحصيلة اللفظية أو لبعد الحصيلة التعبيرية أو للاستبيان ككل، وأنه لا توجد فروق ذات دلالة إحصائية بين متوسطي درجة الاستبيان تعزى لمتغير نوع المؤسسة (خاصة، عمومية)، أو تعزى لمتغير المستوى الدراسي للمربيات (ثانوي، جامعي)، وتوجد فروق ذات دلالة إحصائية بين متوسطي درجة الاستبيان تعزى لمتغير الخبرة المهنية، وأنه يوجد صعوبات متعدّدة لتفعيل استخدام الألعاب التعليمية في تنمية الحصيلة اللغوية بمؤسسات التربية التحضيرية.Abstract:The current study aims to know the role of educational games in developing vocabulary for kindergarten children from the point of view of kindergarten teachers. The study sample consisted of (80) kindergarten teachers. The descriptive approach was used in conducting this study. The researcher also used a questionnaire as a tool to collect data, which he prepared. The results of the study concluded that the teachers’ appreciation was in a high degree for the role of educational games in developing the linguistic singularities of kindergarten children, whether for the dimension of verbal vocabulary or for the dimension of expressive structures or for the questionnaire as a whole, and that there are no statistically significant differences between the average degree of the questionnaire due to the variable of the type of institution (private, general), or attributed to the variable of the academic level of the teachers (secondary, university), and there are statistically significant differences between the average degree of the questionnaire due to the variable of professional experience, and there multiple difficulties for use educational games in developing linguistic vocabulary in preparatory education.
Keywords: الألعاب التعليمية; الحصيلة اللغوية; مربيات أقسام التربية التحضيرية; educational games; vocabulary; kindergarten teachers